2013
DOI: 10.3109/21681805.2013.840857
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral microwave thermotherapy treatment of chronic urinary retention in patients unsuitable for surgery

Abstract: In this study, both the median age and the percentage of patients unsuitable for surgery were larger than in previous studies. Despite this, TUMT relieved 77% of their catheter and 79% reported an improvement in their quality of life. This study shows that TUMT is an effective treatment for patients unsuitable for surgery and with chronic urinary retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Over a 12‐month follow‐up of 121 patients, Law et al found a 75% change in the QoL of the patients after TUNA 30 . In a study in which TUMT was applied to a catheter‐dependent patient group similar to ours, the change in QoL was found as 79% 23 . In the current study, when we compared the before‐treatment and 24th‐month measurements of the catheter‐free group, we detected a 70.6% change in QoL.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Over a 12‐month follow‐up of 121 patients, Law et al found a 75% change in the QoL of the patients after TUNA 30 . In a study in which TUMT was applied to a catheter‐dependent patient group similar to ours, the change in QoL was found as 79% 23 . In the current study, when we compared the before‐treatment and 24th‐month measurements of the catheter‐free group, we detected a 70.6% change in QoL.…”
Section: Discussionsupporting
confidence: 67%
“…Aagaard et al published the 6‐month follow‐up data of 124 patients who were not eligible for surgical treatment and determined the success of TUMT based on the percentage of patients who were no longer dependent on a catheter. They reported that 77% of patients no longer needed a catheter 23 . Similarly, in another TUMT study with a mean follow‐up period of 26 months, urinary retention was resolved in 63.7% of the patients 24 .…”
Section: Discussionmentioning
confidence: 85%
“…Due to the increased operative risk of TURP, as well as AEs for these patients, nonsurgical treatment alternatives are required to meet their needs. Studies in the early 2000s and after reported the first successes with TUMT for urinary retention with TWOC success rates ranging from 72 to 82% [14][15][16][17][18][19]. In a later randomized, controlled trial of catheter-dependent patients treated with TUMT or TURP/enucleation at 6 months of follow-up 79 and 88% of men were catheter free, respectively [18].…”
Section: Discussionmentioning
confidence: 99%
“…The condition is correlated not only with the physiology of aging, but also with comorbidities and their treatment [ 31 33 ]. More than 70% of men over the age of 50 years have various diseases of the prostate, including BPH [ 6 , 12 , 43 ]. In the present study, erectile dysfunction occurred in over 75% of our patients.…”
Section: Discussionmentioning
confidence: 99%